Self-regulatory resource allocation network (SRAN) for Alzheimer detection - Tok, Tee Keong. (2012)
In this project we will be talking about two things, one is about the Alzheimer's Disease (AD) and the other will be about the intergradations of MS Visual Studio and MATLAB.